(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
This study investigated the information needs of postgraduate students and challenges faced in using online databases at Ahmadu Bello University, Zaria. The study has two objectives which are; to identify the information need of postgraduate students in Ahmadu Bello University, Zaria, and to find out the challenges faced by postgraduate students in using online databases. Quantitative research methodology and survey research design were used for the study. The population of the study comprised of two faculties of Ahmadu Bello University Zaria which are Faculty of Education and Social Science, the Postgraduate students in the faculties were two thousand six hundred and seventy (2,670). The sample size of the study is 134 which is 5% of 2670 as opined by Yount (2006). Questionnaire was used as the instrument for data collection. The data collected was analyzed and interpreted using frequency tables and simple percentage. The study revealed that academic information (93.9%) represents significant secondary needs. The analysis identified skill-related challenges as the most significant barriers to effective database usage, with lack of skills (92.9%), and search confusion (91.8%), dominating the obstacles faced by students. The study concludes that postgraduate students require diverse information sources beyond academic materials, and their ability to utilize electronic resources is constrained by skill deficits rather than technological limitations. The research recommends implementing comprehensive information literacy programs and adopting diversified resource management strategies to bridge identified gaps and enhance research productivity among postgraduate students.